Guided Inquiry Model to Enhance Science Literacy of Fifth Graders on the Circulatory System - Komaria, Wafiq Indah; Mansur, Mansur; Setyaningrum, Vidya (Cahaya Ilmu Cendekia Publisher, 2025)
Research Objective: This study aims to describe the science literacy offifth-grade students at Madrasah Ibtidaiyah Swasta Darussalam Pontianak and the application and influence of the guided inquiry model on improving science literacy in the subject of the human circulatory system, including its quantitative influence. Methodology: This study applied a quantitative approach with an experimental method using a nonequivalent control group design. Classes VA and VB were selected as samples through total sampling technique. The instruments included multiple-choice tests, observation sheets, and documentation. Data analysis was performed through descriptive statistical tests, prerequisite tests, and hypothesis testing to examine the effectiveness of the model. General Findings: The results showed that the application of the guided inquiry model had a positive impact on improving the science literacy of fifth-grade students at Madrasah Ibtidaiyah Swasta Darussalam Pontianak. This was indicated by an increase in posttest scores compared to pretest scores, as well as significant paired t-test results (0.000 < 0.05). Although the average N-Gain score was only 40.03% (less effective category), this model still contributed to helping students understand science concepts more actively and structurally. Novelty/Originality of this Research: This study is unique because it examines the effectiveness of the guided inquiry model specifically on science literacy at the madrasah ibtidaiyah level, which has rarely been studied. The focus on the human circulatory system and the application of a quantitative approach in a local context makes this research valuable as an empirical contribution to the development of relevant and contextual science learning models.